2015
DOI: 10.4269/ajtmh.14-0683
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Placebo-Controlled Trial Evaluating Safety and Immunogenicity of the Killed, Bivalent, Whole-Cell Oral Cholera Vaccine in Ethiopia

Abstract: Killed whole-cell oral cholera vaccine (OCV) has been a key component of a comprehensive package including water and sanitation measures for recent cholera epidemics. The vaccine, given in a two-dose regimen, has been evaluated in a large number of human volunteers in India, Vietnam, and Bangladesh, where it has demonstrated safety, immunogenicity, and clinical efficacy. We conducted a double-blind randomized placebo-controlled trial in Ethiopia, where we evaluated the safety and immunogenicity of the vaccine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 26 publications
3
16
4
Order By: Relevance
“…No adverse events or serious adverse events occurred more frequently among vaccinees compared to placebo recipients in either population . The vaccine was shown to be immunogenic in both the Ethiopian and Indian cohorts.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…No adverse events or serious adverse events occurred more frequently among vaccinees compared to placebo recipients in either population . The vaccine was shown to be immunogenic in both the Ethiopian and Indian cohorts.…”
Section: Resultsmentioning
confidence: 86%
“…Details on study agents, sites, procedures and assembly of participants in these individually randomised, double blind, placebo‐controlled trials have been reported previously . In both trials, healthy adults (18 years and above) and children (1–17 years) were recruited.…”
Section: Methodsmentioning
confidence: 99%
“…The baseline vibriocidal titers in the different age groups of vaccinees among the FDMN population were similar when compared to the responses seen in Bangladeshi healthy participants who had received Shanchol in another study (NCT02823899). When compared with results with the results of the FDMNs with other non endemic countries like Ethiopia and Haiti, it is seen that FDMN population had higher baseline vibriocidal geometric mean titer (GMT) to Ogawa (24 vs. 14 vs. 72) as well as Inaba (16 vs.11 vs. 44) serotypes seen in Ethiopia, Haiti and FDMN respectively [24,25]. This result also suggests that the FDMN population were already exposed to Vibrio cholerae O1.…”
Section: Discussionmentioning
confidence: 84%
“…33 Interestingly, this may be directly related to the amount of natural exposure and pre-existing antibodies since higher seroconversion rates were noted following a second dose in comparatively less endemic areas in Haiti and Ethiopia. 29,34,35 This suggests that there may be important geographical differences in immunological response in areas of varying cholera exposure. A phase 3 placebo RCT assessing a single dose of Shanchol in over 200,000 individuals from the hyperendemic setting of Bangladesh found an efficacy of 40% against all cholera cases and 60% protective against cholera cases with severe dehydration over a 6 month period.…”
Section: Modified Killed Whole Cell Only Vaccinesmentioning
confidence: 99%
“…[27][28][29] Shanchol has conferred 67% protection in a double blind randomized placebo controlled trial in more than 67,000 children and adults in Kolkata, India. 30 However, levels of protection were not uniform across all age groups.…”
Section: Modified Killed Whole Cell Only Vaccinesmentioning
confidence: 99%